A Stochastic Immunotherapy Model for Breast Cancer with Pulsed Chemotherapy (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we consider an immunotherapy model for breast cancer with stochastic perturbations and pulsed chemotherapy. By using stochastic Lyapunov analysis and the strong law of large numbers, we first prove theexistence, uniqueness and the stochastic ultimate boundedness of the globalpositive solution for the model. Then we obtain sufficient conditions for theextinction of tumor cells and the persistence of all three kinds of cells for thismodel. Finally, we use numerical simulations to verify the theoretical resultswhich are obtained in the paper.
Keywords: Breast cancer; persistence; extinction; white noise; impulsive effect.